Contributions of the paraventricular thalamic nucleus in the regulation of stress, motivation, and mood - Hsu, David T.; Kirouac, Gilbert J.; Zubieta, Jon-Kar; Bhatnagar, Seema (Frontiers in Behavioral Neuroscience, 2014)
The purpose of this review is to describe how the function and connections of the paraventricular thalamic nucleus (Pa) may play a role in the regulation of stress and negative emotional behavior. Located in the dorsal midline thalamus, the Pa is heavily innervated by serotonin, norepinephrine, dopamine, corticotropin-releasing hormone, and orexins, and is the only thalamic nucleus connected to the group of structures comprising the amygdala, bed nucleus of the stria terminalis, nucleus accumbens, and infralimbic/subgenual anterior cingulate cortex. These neurotransmitter systems and structures are involved in regulating motivation and mood, and display abnormal functioning in several psychiatric disorders including anxiety, substance use, and major depressive disorders. Furthermore, rodent studies show that the Pa is consistently and potently activated following a variety of stressors and has a unique role in regulating responses to chronic stressors. These observations provide a compelling rationale for investigating the Pa in the link between stress and negative emotional behavior, and for including the Pa in the neural pathways of stress-related psychiatric disorders.